ADHERENCE TO PROPHYLAXIS IN RELATION TO QUALITY OF LIFE AND ANXIETY LEVEL IN TURKISH PATIENTS WITH SEVERE HAEMOPHILIA A - Zuhre Kaya (Rojan GÜMÜŞ, 2020)
Background: Bleeding increases anxiety and reduces quality of life (QoL) for patients with severe haemophilia A. This study investigated adherence to prophylaxis in relation to QoL and anxiety level in haemophilia A patients. Methods: Forty-three patients with severe haemophilia A were stratified into three groups by age: 12 children aged 2-13 years, 17 adolescents aged 14-21 years, and 14 adults aged 21-65 years. Quality of life and anxiety level were assessed using the 36-item Short Form Health Survey (SF-36) and the State-Trait Anxiety Inventory (STAI), respectively. Regular prophylaxis (RP) and pharmacokinetic (PK)-guided prophylaxis were prescribed for 30 and 13 patients, respectively. Results: All the children (n=12; nine RP, three PK-guided prophylaxis) and 10 (58.8%, PK-guided prophylaxis) of the adolescents were completely adherent to prophylaxis. Seven (41.2%) of the adolescents and all 14 adults (100%) were non-adherent to prophylaxis. Compared to findings for the adolescents, anxiety level was higher among the children's parents and among the adults (p<0.05 for both). The QoL level was lower for the adults than for the parents of children and for the adolescents (p<0.05 for both). Conclusion: Pharmacokinetic-guided prophylaxis for adults and home treatment for children in haemophilia A would enhance adherence to prophylaxis, increase QoL and reduce anxiety levels.